Tradição e Juventudes em ALAGOAS: o grupo de coco de roda Xique-xique - Cavalcanti, Telma César (2018)
This thesis presents the trajectory of the Coco de Roda Xique-xique’s youth group from the neighborhood of Jacintinho in Maceio, since 2000 and holds today around 90 components. The research sought to understand the dimensions of dance practice in the construction of the identity processes of these young people. Taking the body and the movement as object of analysis from the references of Rudolf Laban (1966, 1978, 1990), the study discusses the recognition and legitimation of hese young Alagoanos as continuing agents of a local cultural tradition, and seeks to collaborate for the formative actions in dance, in this case, giving in socio-cultural environments outside the school. I approach youth as a socio-historic category, dialoguing with authors as Feixa (2004, 2010), Pais (1990, 2003), Reguillo (2000, 2008), among others. It identifies tradition as key category for the problematization of the central questions that guide the research problematized from the dialogue with the propositions of Giddens (1997), among other authors, in interchange with the notion of identity cultures, proposed by Agier (2001). It presents a historical reference on coco Alagoano, trying to show the transits performed by this poetic-musical-choreographic manifestation amid to the relations between tradition and change. On the other hand, is seeks to understand the influences from the Brazilian folkloric movement in the tradition narratives dominant in Alagoas and the possible reverberations about the young people surveyed. In the empirical field of the study on the Xique-xique group, participative observation, a comprehensive interview (KAUFMAN, 2013) and an adapted application of the discussion groups methods were carried out using Weller’s (2006, 2011) references, as well as access to the social network, facebook. It has been verified through analysis on the data produced, that the young people from Xique-xique have been searching for ways to appropriate the knowledge of the old masters, having in them the reference for the legitimation of their dance as they identify themselves as followers of the tradition of the coco alagoano. The practice of this dance and belonging to the group, besides providing opportunities for aesthetic-artistic aspirations, constitute a means of resistance to a common juvenile condition, marked by precarious opportunities for study and work, by living with violence and the marginalization of the neighborhood in which they reside, whose reality fills with stigmas their existences